Christ the Stranger: The theology of Rowan Williams - Delport, Khegan M (Stellenbosch Theological Journal, 2016)
Christ the Stranger: The theology of Rowan Williams by Myers, Benjamin 2012, London-New York: T & T Clark ISBN: 9780567562364